2017
DOI: 10.5692/clinicalneurol.cn-001067
|View full text |Cite
|
Sign up to set email alerts
|

A case of optic perineuritis—A literature review of Japanese cases and clinical problems

Abstract: suppression images demonstrated abnormal enhancement, "tram track" sign on the axial view (arrows) and "doughnut" sign on the coronal view (broad arrow), of the right optic nerve sheath. The similar hyperintensity configurations (arrow heads) to both signs could be recognized on T 2 -weighted MR (C, D, F). These intensity changes were suggested to be due to tissue edema.A: axial T 1 weighted image (1.5 T, TR 654 ms, TE 10 ms), B; contrast enhanced axial T 1 weighted image with fat suppression (1.5 T, TR673 ms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The outcome of steroid treatment is dependent on the time between the appearance of symptoms and initiation of treatment [5,11]. The idiopathic group reportedly had a better convalescence than the second group [14]. In the present case, steroid administration had little effect on the patient's symptoms despite prompt treatment initiation.…”
Section: Discussionmentioning
confidence: 63%
“…The outcome of steroid treatment is dependent on the time between the appearance of symptoms and initiation of treatment [5,11]. The idiopathic group reportedly had a better convalescence than the second group [14]. In the present case, steroid administration had little effect on the patient's symptoms despite prompt treatment initiation.…”
Section: Discussionmentioning
confidence: 63%
“…The “doughnut sign” on the coronal images and the “tram-track sign” on the axial images in orbital MRI indicate optic perineuritis [ 6 , 7 ] or impaired perfusion of spinal fluid around the optic nerve due to compression. It causes symptoms such as ocular pain, visual disturbance, papilledema, eye movement disturbance, and eyelid drooping.…”
Section: Discussionmentioning
confidence: 99%
“…It causes symptoms such as ocular pain, visual disturbance, papilledema, eye movement disturbance, and eyelid drooping. Causes of optic perineuritis include antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis, hypertrophic pachymeningitis, allergic granulomatous vasculitis (Churg-Strauss syndrome), granulomatosis with polyangiitis, and anti-GQ1b antibody syndrome, as well as systemic inflammatory diseases such as Bickerstaff's brainstem encephalitis, osteodysplastic syndrome, aseptic meningitis, and liver cancer [6] . Idiopathic and secondary recurrences are frequent; however, their response to steroids is good.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical findings, VF test, OCT and MRI take an important role in differential diagnosis. 1,2 The diagnosis of OPN is based on clinical and radiological findings. Patients symptoms may consist of sudden or progressive visual loss in one eye accompanied or not by eye pain.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that syphilis, tuberculosis, sarcoidosis, giant cell arteritis, Crohn disease, herpes zoster, Wegener granulomatosis are specific causes of OPN. 1,2,4 Familial Mediterranean fever (FMF) is an auto-inflammatory disease which starts during childhood or adolescence with recurrent poly- serositis attacks. Although it has been reported that uveitis, retinal ischemia, cataract, glaucoma and retinal detachment are related to FMF, optic nerve involvement has been rarely reported in the literature.…”
Section: Discussionmentioning
confidence: 99%